Effect of Price Determinants on World Cocoa Prices for Over the Last Three Decades: Error Correction Model (ECM) Approach - Lya Aklimawati; Teguh Wahyudi (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2013)
High  volatility  cocoa  price  movement  is  consequenced  by  imbalancing between power demand and power supply in commodity market. World economy expectation and market  liberalization would lead to instability on cocoa prices in  the  international  commerce.  Dynamic  prices  moving  erratically  influence the benefit  of market players, particularly  producers. The aim of this research is  (1)  to  estimate  the  empirical  cocoa  prices  model  for  responding  market dynamics and (2) analyze short-term and long-term effect of price determinants variables  on cocoa prices.  This research  was  carried out by  analyzing  annualdata from 1980 to 2011, based on secondary data. Error correction mechanism (ECM)  approach was  used  to  estimate the  econometric  model  of  cocoa  price.The  estimation  results  indicated  that  cocoa  price  was  significantly  affected  by exchange rate IDR-USD, world gross domestic product,  world inflation, worldcocoa production, world cocoa consumption, world cocoa stock and Robusta prices at varied significance level from 1 - 10%. All of these variables have a long run equilibrium relationship. In long run effect, world gross domestic product, world  cocoa  consumption  and  world  cocoa  stock  were  elastic  (E  >1),  while other  variables  were  inelastic  (E  <1).  Variables  that  affecting  cocoa  pricesin  short  run  equilibrium  were  exchange  rate  IDR-USD,  world  gross  domestic product,  world  inflation,  world  cocoa  consumption  and  world  cocoa  stock. The  analysis  results  showed  that  world  gross  domestic  product,  world  cocoa consumption  and  world  cocoa  stock  were  elastic  (E  >1)  to  cocoa  prices  in short-term.  Whereas,  the  response  of  cocoa  prices  was  inelastic  to  change  of exchange rate IDR-USD and world inflation.Key words: Price determinants, cocoa, Error Correction Model, demand, supply, stock